Qualitative Core-periphery Approach on Information Sharing in Multicultural Communities Ecosystem - Aristi, Savira; Ono, Kenta (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
Within interconnected multicultural communities, information sharing plays a pivotal role in shaping social dynamics and cross-cultural exchange. This study employs a qualitative core-periphery approach to explore information sharing patterns within such ecosystems. Focusing on the core nodes and peripheral nodes, we investigate the dynamics of information flow, influential actors, and community cohesion. A case study involving 75 individuals from 11 nationalities reveals central figures' vital role in facilitating communication. Through in-depth interviews and analysis of online and offline interactions, the research identifies the key actors within the communities’ core-periphery structure. The research continues with qualitative network mapping and explores how information sharing occurs within different cultural groups. The core-periphery structure fosters diversity but can also reinforce information inequality. This research is relevant to approach and apply targeted interventions to a new multicultural communities ecosystem and study the patterns of how they share information to each other.